THE EFFECTIVENESS OF THE DIRECT METHOD IN THE PROCESS OF ACQUIRING ARABIC AS THE SECOND LANGUAGE OF THE STUDENTS OF MAMBAUS SHOLIHIN BOARDING SCHOOL ( Review of B.F. Skinner Theory ) - Maf'udah, Syafiyatul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2025)
In order to learn a foreign language, in this instance Arabic, the direct technique is used in this study to describe the effectiveness of the outcomes. B.F. Skinner claimed that language originates from the stimulus-response (S-R) between speakers and listeners using the operand theory. Researchers employ pre-test, treatment, and post-test instruments as part of the experimental research methodology. The study's findings were based on the percentage of Mambaus Sholihin Islamic Boarding School test results that indicated improved performance on the post-test compared to the pre-test following Muhadatsah activities. Second Language Acquisition (SLA) is the process of learning a second language. The aim of this study is not to assert that this approach is the most correct and effective in SLA, but rather to show that this method and theory is one of the most effective ways. Do not exclude the possibility that other approaches and theories could also be used successfully. Keywords: Direct Method, Skinner Operant Model, Pondok Mambaus Sholihin, Muhadatsah Activities